168 Exploring the Role of Microrna-21 On Human Saphenous Vein Smooth Muscle Cell Function. (31st May 2014) - Alshanwani, Aliah; Riches, Kirsty; Wood, Ian; Turner, Neil; Porter, Karen
Abstract : Introduction: MicroRNAs (miRs) are short, non-coding RNAs that negatively regulate gene expression and are reportedly dysregulated in pathological conditions. MiR-21 is expressed throughout the cardiovascular (CV) system and particularly in vascular smooth muscle cells (SMC). Altered SMC function is pivotal to adaptation of saphenous vein (SV) bypass grafts, aberrancies of which may compromise patency rates. The aim of this study was to explore the potential role of miR-21 in human SV-SMC function. Methodology: Cultured SV-SMC from multiple patients were exposed to PDGF-BB for 24–72 h before measuring miR-21 expression levels. In further experiments, an 84-gene microarray analysis of SMC overexpressing miR-21 (premiR-21 transfection) was performed. Significant changes in selected targets were confirmed using real time RT-PCR and Taqman primers. Result: PDGF-BB (10 ng/ml) significantly augmented miR-21 expression (P < 0.05, n = 5), an effect abolished by inhibition of either the AKT or ERK signalling pathways. In premiR-21 transfected SMC, a 90% reduction in the proinflammatory cytokine IL-1α (P = 0.13, n = 6) and 6-fold increase in matrix metalloproteinase MMP-1 (P < 0.05, n = 6) mRNA levels were observed relative to control (premiR negative transfected) cells. Comparable changes were mirrored in native SV-SMC treated with PDGF. Conclusion: PDGF increased miR-21 expression via AKT and ERK pathway activation. Elevated levels of miR-21 downregulated IL-1α but upregulated MMP-1 gene expression in human SV-SMC. Understanding the stimuli and molecular mechanisms that promote aberrant miR-21 expression, its effects on downstream mRNA targets and ultimately on SMC function may reveal novel therapeutics to target adverse SV graft remodelling.